Emergency Autonomous Steering Control Research Based on Receding Horizon H∞ Control and Minimax Criteria - Yi Xu (IEEE, 2021)
Aiming at the problems of model uncertainty, external interference of road conditions, and inherent nonlinearity of lateral movement of autonomous driving vehicles, this paper proposes an effective control technology for an automatic steering system, namely, the receding horizon $H_{∞ }$ control, which has good path tracking performance and can overcome external interference. First, a two-degree-of-freedom vehicle model and a road model are established. Then, the Hamilton equation is established using Pontriagin’s minimum principle, and the optimal control solution and the most serious disturbance are solved based on the minimax principle. Finally, in order to evaluate the receding horizon $H_{∞ }$ autonomous steering control method, lane change simulation and hardware in the loop simulation are developed to describe the effect of receding horizon $H_{∞ }$ . The simulation results show that the model predictive control (MPC) and linear matrix inequality (LMI) controller will exhibit oscillation and instability under the condition of external interference. To improve the stability, the $H_{∞ }$ controller reduces part of the performance, while the rolling horizon $H_{∞ }$ strategy can ensure the robustness of automatic steering and has a certain anti-interference performance.